Innovation, development, and financing of institutions of Higher Education in health - Mario Roberto Dal Poz; Maria Helena Costa Couto; Thais de Andrade Vidaurre Franco
Abstract: The article analyzes the configuration and trends in institutions of Higher Education and their relationship as components of the Health Economic-Industrial Complex (HEIC). The expansion of higher education is part of the transition from elite to mass systems, with tensions between quantitative and qualitative aspects. Such changes reflect different cultures and are related to international phenomena such as globalization, economic transformations, the development of new information and communication technologies, and the emergence of an international knowledge network. The scale and content of these changes vary according to the expansion and institutional reconfiguration of educational systems, as well as the link between state and society. Market expansion for private higher education stirs competition, shapes business clusters, modifies training processes, and raises new public policy challenges.